Evaluation methods for retroreflectors and quantitative analysis of near-infrared upward reflective solar control window film — Part I: Theory and evaluation methods. (15th May 2017) - Harima, Tatsuya; Nagahama, Tsutomu
Highlights: Upward and downward reflectivities as reflection characteristics for walls are proposed. Upward reflectivity is obtained through evaluation methods using an integrating sphere. The reflectivities for retroreflectors at large incident polar angles are obtained. Abstract: In recent years, research has been actively conducted on the application of cool materials that have high solar reflectivity and high thermal emittance to building envelopes (roofs and walls) and other surfaces in the urban environment. They have been applied to decrease solar absorption and increase the urban albedo as an effective technique to mitigate the Urban Heat Island effect and to reduce global warming. It has been a concern that reflected solar radiation onto the streets (downward reflection) leads to thermal environmental deterioration of pedestrian spaces. In cases where building facades have specular or diffusive reflectivity, solar radiation is reflected downward to pedestrian spaces. As there is currently a lack of evaluation methods for such retro-reflective materials, this study mainly aims at developing evaluation methods and measurements of reflectivity and transmissivity properties of retro-reflective materials. This required further development of evaluation methods and the apparatus including an integrating sphere, allowing the measurement of directional-hemispherical spectral reflectivity (DHSR) at large incident polar angles that are equivalent to the daytime solar elevation at a south-facing vertical surface, as well as the selective measurement of spectral reflectivity in the upward direction with the horizontal plane as the boundary. Furthermore, evaluation methods of DHSR including the retro-reflected beam that leaks from the incident opening are developed with a new measurement method using an integrating sphere and half mirror. This article mainly describes theory and methods of the above-mentioned evaluation, and evaluates results of beam leakage compensated DHSR. Verification of the measurement results is discussed in Part II of this article, together with the properties and effects of the upward reflective solar control window film that was evaluated in this study.